Kinematic changes during a 100-m Front crawl: Effects of performance level and gender - Seifert, L.; Chollet, D.; Chatard, J. C. (Medicine & Science in Sports & Exercise, 2007)
Purpose: This study analyzed kinematic changes during a 100-m front crawl to investigate the effects of performance level and gender, comparing 12 high-speed males, 8 medium-speed males, 8 low-speed males, and 8 high-speed females.